Screening and selection of potential carriers to immobilize Aureobasidium pullulans cells for fructo-oligosaccharides production - Castro, C. C. (2017)
Fructo-oligosaccharides (FOS) are non-digestible sweeteners with improved functional and technological properties for food and pharmaceutical industry applications. The immobilization of FOS-producing microorganisms whole cells can be used to improve the production of FOS and so, an accurate choice of the carrier is of crucial importance. Here we present a screening and selection of carriers for immobilization of Aureobasidium pullulans cells with potential for yielding high FOS production. Synthetic, agro-industrial by-products and mineral materials were tested and selected regarding their ability to immobilize cells, as well as their potential to produce FOS, through shaken-flask fermentations. Increased amounts of immobilized cells were found for carriers with higher porosity observed at the microscope, higher water absorption index (WAI) and lower critical humidity point (CHP). Reticulated polyurethane foam was one of the most efficient synthetic carriers immobilizing cells (over 75% (w/w) of the total cells were immobilized). Also, high FOS production was obtained: FOS concentration, purity and yield increased in 15, 8 and 12% (w/w), respectively, as compared to free cells conditions. Although walnut shell had a much lower immobilization efficiency, the high amount of cells grown while using this carrier led to a highest increment of FOS concentration, purity and yield, namely, 27, 10 and 25% (w/w). Cells immobilization with the selected carriers holds great promise for FOS production on a larger scale.